INFLUENCE OF 1% METACYRIC ACID ETHER AND FULLERENE C60 ON THE MORPHOFUNCTIONAL STATUS OF THE RATS’ LIVER - Silenko, B.Yu.; Silenko, Yu.I.; Yeroshenko, G.A. (World of Medicine and Biology, 2019)
In the work the effect of fullerene C60 as a potential hepatoprotector on the structural organization of the liver of rats was studied in comparison with the monomer for hot polymerization plastics. It was found that the long-term supply of residual monomer from the base of acrylic prostheses causes dystrophic changes in hepatocytes and disorders of hemomicrocirculation in the liver of rats. The use of fullerenes 60 against the background of the action of 1% methacrylic acid ester reduces dystrophic changes in hepatocytes and discirculatory manifestations in the hepatic lobules, therefore, it can be considered as a protector of the digestive system when using full and partial dentures.